Las rondas como estrategias didácticas en el periodo de adaptación con los niños y niñas de 3 a 4 años en la unidad educativa comunitaria intercultural Bilingüe Surupucyu parroquia Guanujo cantón Guaranda provincia Bolívar periodo lectivo 2018-2019. - Manobanda Chimbo, Maria Rosa (2019)
The rounds are very important for the adaptation of children who come from different homes to initial education, these activities also develop creativity and imagination therefore help for their better learning. In the rural sector, the teacher must master Spanish and Kichwa to be able to interact and communicate with the children from the beginning of the school year. The period of adjustment is the one that costs the most, in which the teacher demonstrates all her professionalism since, if a child adapts quickly to the new environment, she will have an active participant in the teaching work and in the teaching-learning process. And the best way for children aged 3 to 4 years to adapt to Initial I is through play and especially with rounds. In the educational institution games are very important for young children who adapt to the school environment the teacher should be dynamic, creative and have patience with them, take them to green spaces, to perform playful activities, in that way to involve all the boys and girls in the rounds. In the intervention that we made with the children of the U.E. Surupucyu del Initial 1 we could realize that the more time children spend communicating through the rounds the faster they adapt to the school environment. Conduct the rounds as a didactic strategy in the adaptation period with the children to facilitate the learning process in the initial education. We conclude that with the application of the rounds in the educational institution, it will be better to adapt to the new environment with the children and with the teacher